Digital Surveillance in Information System Research: A Hybrid Systematic Literature Review and Bibliometric Analysis - Rika Mulyati; Muharman Lubis; Sinung Suakanto; Andriana Andriana; Ni Ketut Caturwati (Indonesian Scientific Journal, 2026)
The advancement of digital technology has promoted the application of digital surveillance in many fields, including public health and social risk management. Nonetheless, little research has comprehensively mapped the field of digital surveillance studies. This paper seeks to investigate the publications, scientific structures, and significant topics of digital surveillance research through a systematic literature review integrated with bibliometric and thematic analyses. Records retrieved from Scopus, 2009-2025resulted in 286 articles that fulfilled the inclusion criteria. Bibliometric analysis was performed using VOSviewer to identify publication trends, main scientific fields, and relationships between keywords. Meanwhile, thematic analysis using NVivo was used to reveal research themes and sub-themes. The results showed that digital surveillance publications had increased significantly since 2020. Social sciences, medicine, and computer science dominated the publications. Thematic analysis revealed that the main research themes focused on the application of digital surveillance in public health, data and information system management, and the use of digital technology. However, issues of governance, ethics, and privacy protection were still underexplored. These findings contribute theoretically by mapping the landscape of digital surveillance research and, practically, by helping academics and practitioners identify opportunities for research and policy development that pay greater attention to ethical and digital governance aspects.